Management of Non-Performing Assets in Regional Rural Banks - A Case Study of Pandyan Grama Bank (PGB), Virudhunagar, Tamil Nadu - Suresh, R. (Indian Journal of Finance, 2010)
There is a general concept commonly accepted "A Man or Woman with no money is equal to a dead body ". Here it is suitable to insist the importance of money; a Rumanian Proverb says that "A Man without money is like a bird with no wings". The basic functions of banks are accepting all kinds of deposits and supply money- "The life blood of business concerns" by lending process. Basically, India is an agriculture based country. Agriculture and its aided activities like cottage, small scale industries play a dominant role in the Indian economy. The Gross Domestic Product of India is occupied up to 60% - 70% by the agricultural income. Whatever it may be for long term and short term capital requirement, money is highly essential. The banks supply the money for all activities. To concentrate on the development of the rural economy, the Government of India extended help for the rural farmers, artesians, entrepreneurs by opening region rural banks, in addition to commercial banks and cooperative banks. In India, regional rural banks are functioning since 1975.